ARTIKEL REVIEW: PENGARUH VARIASI KONSENTRASI BAHAN PENGIKAT PADA FORMULASI TABLET KUNYAH TERHADAP SIFAT FISIK SEDIAAN - Ayyun, Kurrota; Ayisah , Siti; Imami , Muhammad Rizky; Azkiyah , Sovia Maulina; Maghfiroh, Nur lailatul; Putri , Nadiya Kamiliya; Virginia T.K , Rosa; Ambari , Yani; Rahmawati , Dewi; Jalmav , Marthy Meliana Ariyanti; Mubarak , Muhammad Fithrul (Seroja Husada: Jurnal Kesehatan Masyarakat, 2024)
Background Currently, the development of chewable tablets is one of the existing solutions to make tablets easy to consume. Therefore, many chewable tablet formulations have been developed to meet patient needs. This review article presents one chewable tablet formulation and its evaluation using wet granulation and direct compression methods. The purpose of preparing this review article is to determine the effect of binders on the physical stability of the resulting tablet preparations. This article review comes from searches of journals, supporting literature obtained from reference books and online-based search instruments using Google such as Google Scholar spanning the last 10 years. Studies show that the concentration of binder and the choice of binder used in making tablets greatly influences the physical properties of tablets, namely providing excellent disintegration time and tablet hardness. Results So it can be concluded that starch, PVP, gelatin, methocel E-5, amprotab, eudragit E-100, porang starch used as a binder and the extract used are rich in antioxidants and can provide good physical stability and health benefits.